2022
DOI: 10.3390/biomedicines10051122
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Analysis of Circulating Antimicrobial Resistance Genes in Vancomycin-Resistant Enterococcus (VRE) during the COVID-19 Pandemic

Abstract: COVID-19 offers ideal premises for bacteria to develop antimicrobial resistance. In this study, we evaluated the presence of several antimicrobial resistance genes (ARG) in vancomycin-resistant Enterococcus (VRE) isolated from rectal swabs from patients at a hospital in Cluj-Napoca, Romania. Rectal swabs were cultivated on CHROMID® VRE (bioMérieux, Marcy—l’ Étoile, France) and positive isolates were identified using MALDI-TOF Mass Spectrometry (Bruker Daltonics, Bremen, Germany) and further analyzed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Previous works have reported that worldwide, the frequency of the vanA gene is higher; however, in a study in Germany in the COVID-19 pandemic, the presence of the vanB gene was detected in high frequency [ 140 ]. Moreover, other studies in Czech Republic and Romania identified the vanA and vanA/vanB genes, respectively, in Enterococcus isolates [ 141 , 153 ]. Therefore, it is important to emphasize that the epidemiology from region to region is different, so the use of molecular tools is essential because this can help us to understand the distribution of resistance genes and could have an impact on the treatment of patients.…”
Section: Enterococcusmentioning
confidence: 99%
“…Previous works have reported that worldwide, the frequency of the vanA gene is higher; however, in a study in Germany in the COVID-19 pandemic, the presence of the vanB gene was detected in high frequency [ 140 ]. Moreover, other studies in Czech Republic and Romania identified the vanA and vanA/vanB genes, respectively, in Enterococcus isolates [ 141 , 153 ]. Therefore, it is important to emphasize that the epidemiology from region to region is different, so the use of molecular tools is essential because this can help us to understand the distribution of resistance genes and could have an impact on the treatment of patients.…”
Section: Enterococcusmentioning
confidence: 99%
“…Considering all these factors, it is also important to note that during the COVID-19 pandemic there was an increase in antimicrobial usage in order to fight these secondary infections, which means that a corresponding increase in bacterial resistance to these compounds is also to be expected [ 229 ]. This has been reflected in the enterococcal population with reports of increments in highly resistant strains of Enterococcus [ 233 ], including VRE [ 234 ].…”
Section: Covid-19 and Enterococcusmentioning
confidence: 99%
“…They also constitute the second most commonly reported cause of surgical wound infections and the third most often reported cause of bacteremia [33,34]. Moreover, enterococci have been reported as the main Gram-positive bacteria causing hospital-acquired infections during and after the COVID 19 pandemic [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%